AlGaN/GaN HEMTs on diamond substrate with over 7 W/mm output power density at 10 GHz. Issue 20 (1st September 2013) - Dumka, D.C.; Chou, T.M.; Faili, F.; Francis, D.; Ejeckam, F.
Abstract : Record RF performance of AlGaN/GaN high electron mobility transistors (HEMTs) on a diamond substrate with over 7 W/mm output power density at 10 GHz is reported. It is achieved along with the peak power‐added‐efficiency over 46% and power gain over 11 dB for 2 × 100 µm gate‐width HEMTs at 40 V drain bias. Device wafers are prepared by first removing the host Si (111) substrate and nitride transition layers beneath the channel, depositing a 50 nm dielectric onto the exposed GaN buffer, and finally growing 100 µm of a chemical vapour deposition diamond onto the dielectric adhering to the epitaxial AlGaN/GaN. This approach enables the active GaN channel to be brought within 1 µm of the diamond substrate. Test HEMTs are fabricated using a dielectrically defined 0.25 µm gate length process.